2016
DOI: 10.12659/msm.897164
|View full text |Cite
|
Sign up to set email alerts
|

Potential Diagnostic and Prognostic Value of Plasma Circulating MicroRNA-182 in Human Glioma

Abstract: BackgroundPrevious studies showed the aberrant expression of microRNA-182 (miR-182) in glioma tissue. However, the exact role of circulating miR-182 in glioma remains unclear. Here, we confirmed the expression of plasma circulating miR-182 in glioma patients, and further explored its potential diagnostic and prognostic value.Material/MethodsReal-time quantitative PCR (RT-PCR) was used to measure circulating cell-free miR-182 from 112 glioma patients and 54 healthy controls.ResultsOur findings showed that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
1
31
1
Order By: Relevance
“…Knockdown of either miR-20a or miR-106a was observed to increase TIMP-2 expression and consequently inhibit glioma stem cell invasion. Xiao et al found that high levels of plasma miR-182 were associated with poor overall survival ( P  = 0.034) and disease-free survival ( P  = 0.013) among glioma patients [24]. However, in our study, we found that decreased levels of miR-182 were associated with poor overall survival ( P  = 0.037) and disease-free survival ( P  = 0.043) among glioblastoma patients.…”
Section: Resultscontrasting
confidence: 77%
“…Knockdown of either miR-20a or miR-106a was observed to increase TIMP-2 expression and consequently inhibit glioma stem cell invasion. Xiao et al found that high levels of plasma miR-182 were associated with poor overall survival ( P  = 0.034) and disease-free survival ( P  = 0.013) among glioma patients [24]. However, in our study, we found that decreased levels of miR-182 were associated with poor overall survival ( P  = 0.037) and disease-free survival ( P  = 0.043) among glioblastoma patients.…”
Section: Resultscontrasting
confidence: 77%
“…The existence of similar correlations has been demonstrated by many other researchers, including: miR19, miR137, miR144-3p, and miR182 [98][99][100][101]. It was also found that the relationship between the stage of tumor histology is positive for miR19 and miR182, and negative for le7e, miR145 and miR181a [102,103]. This would provide valuable guidance on the characteristics of the tumor before surgery and histopathological examination of the slice, giving the chance for better planning of the procedure.…”
Section: Biomarkerssupporting
confidence: 78%
“…Subsequently, we assessed the remaining 254 full‐text articles and excluded 226 studies based on the exclusion criteria, including 30 meetings, and 196 without clinical data to make a 2 × 2 contingency table. In total, 28 studies were ultimately included in this study . A flowchart of the selection process for this study is presented in Figure .…”
Section: Resultsmentioning
confidence: 99%